PEMANFAATAN POTENSI ARSITEKTUR RUMAH LIMASAN DALAM PENGEMBANGAN DESA WISATA BERKELANJUTAN DI KALURAHAN MANGUNAN – KABUPATEN BANTUL - Yusnita Nugroho, Nancy; Suryono Sombu, Alwin; X, Fransiscus; Hendrawan, Christianto; Xaverius Budi Pangarso, Fransiscus (Jurnal Riset Arsitektur, 2024)
Abstract - In the development of tourism villages, it is necessary to study the local potential that can be raised to empower the community, give a distinctive feature to local local tourism, while still emphasizing sustainable principles, including cultural preservation. Mangunan Village located in Bantul District – Yogyakarta Province has local Javanese architectural characters (including Limasan House Architecture) which can be appointed as one of the tourist attractions. For this purpose, documentation, studies of the condition of existing buildings, as well as studies of the potential and constraints of their use more broadly/long-term in supporting tourism. In addition, tourism development policies that have been implemented also need to be evaluated in order to improve the development plan of Mangunan Tourism Village. Keywords: Tourism Village, Sustainable Tourism, Limasan Architecture, Mangunan